Professional Development for Primary Teachers in Science and Technology
IX, 305 p.
Keywords: This book presents the research output of the Dutch project VTB-Pro, an internationally-oriented project that aimed at providing primary school teachers with the knowledge, abilities and attitudes that are necessary to implement science and technology education in their classes. An introductory chapter by Wynne Harlen and Pierre Lena positions this project in the international context. From the Foreword by Dr. Michel Rocard: I have been pleased to discover the VTB-Pro three-years project carried in the Netherlands (Broadening technological education in primary school). Focusing on professional development of teachers and presenting first hand testimonies and research, the present book demonstrates how to deal with this issue, so critical for a renewed pedagogy. With proper methods, the knowledge of science, the interest in science and technology, the pedagogical skills can all be improved among teachers who often have no or little affection for science.